Implementation of Pamsimas: Realizing the Sustainability of Drinking Water and Sanitation in Villages - Pane, Chairunnas; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2024)
The purpose of this study is to assess the implementation of Community-Based Drinking Water and Sanitation Provision (Pamsimas) in Sidomulyo Village, Krian District, Sidoarjo Regency. This qualitative research provides an overview of the implementation process in the village. Data was collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and data verification techniques proposed by Miles and Huberman. The results indicate that communication, resources, disposition, and bureaucratic structure are key indicators of Pamsimas implementation in Sidomulyo Village. Communication is smooth, resources are sufficient, residents are committed, and the bureaucratic structure adheres to standard operating procedures. These findings have implications for the successful implementation of Pamsimas in similar contexts, highlighting the importance of effective communication, adequate resources, community engagement, and adherence to standard procedures Highlight : Effective communication is a key indicator of successful Pamsimas implementation. Adequate resources are necessary for the implementation of Pamsimas. Adherence to standard operating procedures is crucial for the successful implementation of Pamsimas. Keywords: Pamsimas, implementation, community-based, drinking water, sanitation.